Analisis Pelaksanaan Prinsip Kehati-Hatian (Prudential Principles) Dalam Penyaluran Pembiayaan Akad Murabahah Pada PT. Bank Sumut Syariah KCP Stabat - Nurul Sifana, Rani Febriyanni, Khairunnisa (Pusdikra Publishing, 2022)
This study aims to determine the distribution of financing for murabahah contracts, prudential principles and obstacles in their implementation at PT. Bank SUMUT Syariah KCP Stabat. The research method used in this study is a descriptive qualitative research method with an empirical approach. Informants in this study were employees of PT. Bank SUMUT Syariah KCP Stabat. The results of the study explain that the distribution of murabahah contract financing at PT. Bank SUMUT Syariah KCP Stabat is almost the same as the distribution of financing in general, namely starting with an application, survey and disbursement, while financing products that use a murabaha contract are motor financing, car purchases, purchases of electronic goods, purchases of business raw materials, and purchases for home renovations. PT. Bank SUMUT Syariah KCP Stabat has implemented the precautionary principle in murabahah financing through the 5C aspects, namely Character, Capacity, Condition of Economy, Capital, Collateral, and 7P, namely Personality, Party, Purpose, Prospect, Payment, Profitability, Protection, as well as added aspects 1S namely Sharia. The obstacles that often occur at PT. Bank SUMUT Syariah KCP Stabat in applying the precautionary principle in providing murabahah contract financing consists of internal factors (originating from the bank) and external factors (derived from customers).